2008
DOI: 10.1537/ase.070323
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetric cranial variation in human skeletal remains associated with Okhotsk culture

Abstract: Population affinities and biological variation in human skeletal series associated with the Okhotsk culture from Hokkaido and Sakhalin Islands from the 5th to 12th centuries AD are investigated using 19 nonmetric cranial traits. The Okhotsk crania have a higher frequency of the supraorbital foramen than the Hokkaido Ainu and Jomon, while the frequency of the transverse zygomatic suture vestige in the Okhotsk is as high as in the Jomon. The mean measure of divergence between the northern and eastern Okhotsk cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 80 publications
9
48
1
2
Order By: Relevance
“…The Okhotsk people were sedentary hunter-gatherer-fishers with a characteristic significant dependence on marine resources, and lived in a harsh environment with subzero winter temperatures (Hudson, 2004). Biometrics (Ishida, 1996;Komesu et al, 2008;Kudaka et al, 2013) and ancient DNA (Sato et al, 2009) analyses have revealed strong similarities among Okhotsk people and populations from the lower Amur River region and the Neolithic Baikal. They spread along the coastline from southern Sakhalin to the Okhotsk coast of eastern Hokkaido and the Kuriles during 600-700 AD (Yamaura and Ushiro, 1999).…”
Section: Okhotsk Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The Okhotsk people were sedentary hunter-gatherer-fishers with a characteristic significant dependence on marine resources, and lived in a harsh environment with subzero winter temperatures (Hudson, 2004). Biometrics (Ishida, 1996;Komesu et al, 2008;Kudaka et al, 2013) and ancient DNA (Sato et al, 2009) analyses have revealed strong similarities among Okhotsk people and populations from the lower Amur River region and the Neolithic Baikal. They spread along the coastline from southern Sakhalin to the Okhotsk coast of eastern Hokkaido and the Kuriles during 600-700 AD (Yamaura and Ushiro, 1999).…”
Section: Okhotsk Culturementioning
confidence: 99%
“…To eliminate skeletons from periods other than that of the Okhotsk culture, radiocarbon dating of the Moyoro human skeletons was performed at NIES-TERRA, the accelerator facility of the Institute of Environmental Studies, Ibaraki, Japan (Yoneda et al, 2004b;Komesu et al, 2008). Corrections of +382 ± 16 years for the local reservoir effect (Yoneda et al, 2001) and 90% contribution from marine proteins were applied considering the marine reservoir effect on the 14 C age.…”
Section: Skeletal Samplesmentioning
confidence: 99%
“…metrically expressed by a large, high face, flat nasal bones, and large maxillary and zygomatic bones (Kodama, 1948;Yamaguchi, 1974;Ishida, 1988), and nonmetrically by a high frequency of the supraorbital foramen, hypoglossal canal bridging, transverse zygomatic-suture vestige, and mylohyoid bridging (Kozintsev, 1990(Kozintsev, , 1992Ishida, 1996;Komesu et al, 2008). Recent analyses of mitochondrial DNA (Sato et al, 2007) and nonmetric cranial traits by application of the R-matrix method (Komesu et al, 2008) reconfirmed the close relationships of the Okhotsk prehistoric series with those of the lower Amur River basin, and furthermore suggested possible relationships to more northern Asians, including the Koryak (north of Kamchatka). Additionally, considerable genetic and phenotypic contributions to the recent Ainu were also revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 Genetic relationships among the 10 populations determined on the basis of principal component analysis of ABO allele frequencies. Data of Japanese, 22 Han, 23 Kazakh, 23 Uygur, 23 Balopa, 25 Gidra, 25 [42][43][44][45] and mtDNA data, 31,32 the Okhotsk people could have originated from the Sakhalin Island and from lower regions of the Amur River in East Siberia. This indicates that the frequency of O alleles among ancestors of those populations might have been high.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Similarly, morphological and genetic studies indicate that the Okhotsk people could have originated from eastern Siberia as well. 31,32,[42][43][44][45] The Jomon/Epi-Jomon and Okhotsk people were, however, located far from each other, as shown in the PC analysis (Figure 3). Although the Jomon/Epi-Jomon people and Okhotsk people shared the five alleles, the frequencies were considerably different from each other.…”
Section: Discussionmentioning
confidence: 99%